Macronyssus kolenatii - Orlova, Maria V.; Anisimov, Nikolay V. (Zenodo, 2023)
Macronyssus kolenatii (Oudemans, 1902) Distribution – Russia (Stanyukovich 1997), Europe (Radovsky 1967; Stanyukovich 1990), Caucasus (Armenia) (Ogadjanian and Arutyunian 1974), Asia (Kazakhstan, Uzbekistan) (Stanyukovich 1997), Africa (Egypt) (Radovsky 1967). Hosts – Pipistrellus pipistrellus (Radovsky 1967; Stanyukovich 1990), Pi. pygmaeus , Pi. nathusii (Stanyukovich 1990), Pi. kuhlii (Radovsky 1967), My. dasycneme , and My. brandtii (Stanyukovich 1990), My. mystacinus (Stanyukovich 1997), Vespertilio murinus , and Eptesicus nillsoni (Stanyukovich 1997). Published as part of Orlova, Maria V. & Anisimov, Nikolay V., 2023, Three new species of bat-parasitic gamasid mites of the genera Spinturnix, Macronyssus and Steatonyssus (Acari: Mesostigmata: Spinturnicidae, Macronyssidae) from Siberia and Mongolia, with keys to species of Russia and adjacent countries, pp. 211-239 in Persian Journal of Acarology 12 (2) on page 225, DOI:10.22073/pja.v12i2.76740, http://zenodo.org/record/8113590